2009
DOI: 10.1038/nrneurol.2009.175
|View full text |Cite
|
Sign up to set email alerts
|

Changing perspectives regarding late-life dementia

Abstract: Individuals over 80 years of age represent the most rapidly growing segment of the population, and late-life dementia has become a major public health concern worldwide. Development of effective preventive and treatment strategies for late-life dementia relies on a deep understanding of all the processes involved. In the centuries since the Greek philosopher Pythagoras described the inevitable loss of higher cognitive functions with advanced age, various theories regarding the potential culprits have dominated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
219
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 267 publications
(232 citation statements)
references
References 110 publications
11
219
0
2
Order By: Relevance
“…There are relatively few treatments to delay or mitigate the memory impairments that accompany dementia and pharmacological strategies have not had a major impact in this area. 3 In the current study, we describe a paradigm of physical and cognitive activity that reduces memory impairments and normalizes altered hippocampal CA1 pyramidal cell structure in a model of VasD using older animals. Whether these findings support a 'use-it or lose-it' 6 or 'cognitive reserve' 48 hypothesis is difficult to ascertain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are relatively few treatments to delay or mitigate the memory impairments that accompany dementia and pharmacological strategies have not had a major impact in this area. 3 In the current study, we describe a paradigm of physical and cognitive activity that reduces memory impairments and normalizes altered hippocampal CA1 pyramidal cell structure in a model of VasD using older animals. Whether these findings support a 'use-it or lose-it' 6 or 'cognitive reserve' 48 hypothesis is difficult to ascertain.…”
Section: Discussionmentioning
confidence: 99%
“…To date, pharmacological and immunologic interventions have met with limited success in reducing mild cognitive impairments and dementia in patient populations. 3 More promising, however, is the theory that physical exercise, 4 cognitive activity, 5 or a combination of both, improves cognition and may potentially delay the progression of mild cognitive impairments. 6 In a prospective study of cognitively normal participants, baseline physical activity was associated with lower rates of dementia at 5 years, and there was a negative correlation between the intensity of exercise and cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with the findings of Solas et al, and suggests that parallel lines can be drawn between behavioral outcome in rodent and human models for aging, as similar stressors appear to have long-term effects in both species. Fotuhi et al (2009) suggested that a multitude of internal (genetic) and external (environmental) factors increase or decrease the cerebral blood flow, pro-and anti-inflammatory cytokines, insulin-signaling components, growth factors, cortisol, etc., leading to a congruence of physiological processes in the brain making up human learning and memory parameters. As most of the external factors can be controlled in animal models, we often use rodent models for examining the cognitive effects of certain drugs or specific external factors under controlled conditions.…”
mentioning
confidence: 99%
“…The disadvantage of studying the effects of a specific factor in humans is that cognitive performance in humans is influenced by many factors such as culture, upbringing, education, diet habits, amount of exercise and other activities, as well as motivation and ambition. 'The dynamic polygon hypothesis' for human aging has recently been formulated to describe this cluster of genetic and environmental factors responsible for varying degrees of age-related dementia (see, eg, Fotuhi et al, 2009). The authors proposed that a balance of positive and negative factors can affect the brain throughout the lifespan to determine cognitive performance late in life.…”
mentioning
confidence: 99%